Development of the Potential of Telang Flowers for an Empowerment-Based Herbal Market in Sumberlawang District, Sragen, Central Java - Dewi Ismoyowati; Nurul Istiqomah; Izza Mafruhah (Journal of Innovation and Community Engagement, 2023)
Developing a local resource-based potential by encouraging community involvement is the right choice to maintain environmental sustainability while providing optimal benefits for local communities. This community service aims to (1) develop the potency of the butterfly pea (telang) flower as herbal food; (2) increase the economic potential of the telang flower; (3) provide community economic empowerment; and (4) provide student involvement in MBKM. The community service was carried out by applying training and mentoring methods, involving local government partners and the community. Meanwhile, in implementing the method in the field, the community becomes the main actor in designing and analyzing their potential and problems for the purpose of creating innovative products that will provide added value and competitiveness. The result of this service is that the community understands the potential of the butterfly pea flower for example being able to create food and drink by using the flower to increase economic value and have an impact on people's welfare.